2017
DOI: 10.1016/j.genhosppsych.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and its components among patients with various psychiatric diagnoses and treatments: A cross-sectional study

Abstract: The prevalence of MetS and its components among patients with psychiatric disorders is alarming irrespective of their diagnoses. Thus, metabolic screening especially among high risk groups is critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
2
19
1
Order By: Relevance
“…A recent cross-sectional comparative study on the prevalence of MetS in patients maintained on AP in Qatar showed a higher level of BMI but similar measures of BP, fasting glucose, TG, and HDL (Hammoudeh et al 2018) when compared to our retrospective study. A Saudi study conducted on psychiatric patients also reported higher BMI (28.6 ± 7.7 kg/m 2 ), and fasting blood glucose (6.16 ± 2.48 mmol/L) when compared to ours (Alosaimi et al 2017). There are no other studies from the countries of the Arabic Peninsula (usually have similar ethnicity distribution) that compared the effects of various AP on the metabolic measures.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…A recent cross-sectional comparative study on the prevalence of MetS in patients maintained on AP in Qatar showed a higher level of BMI but similar measures of BP, fasting glucose, TG, and HDL (Hammoudeh et al 2018) when compared to our retrospective study. A Saudi study conducted on psychiatric patients also reported higher BMI (28.6 ± 7.7 kg/m 2 ), and fasting blood glucose (6.16 ± 2.48 mmol/L) when compared to ours (Alosaimi et al 2017). There are no other studies from the countries of the Arabic Peninsula (usually have similar ethnicity distribution) that compared the effects of various AP on the metabolic measures.…”
Section: Discussionsupporting
confidence: 42%
“…A study on patients with various psychiatric disorders from Saudi Arabia showed that the prevalence of the metabolic measures was not different when compared to those not taking AP. However, the intake of SGA was mainly associated with elevated BP (Alosaimi et al 2017). This variability in the changes of metabolic risk factors among the various studies could be attributed to several factors: genetics, ethnicity, age, gender, type of mental illness, type and dose of AP, duration of treatment, concomitant medications, family history of metabolic disorder, smoking, lifestyle, eating habits, etc.…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, our results are consistent with to those of Alosaimi et al . () who surveyed 992 patients with serious mental illness (41.2%) in Saudi Arabia, but lower than that reported by John et al . () in 203 patients with serious mental illness (54.0%) in Australia, by Kumar et al .…”
Section: Discussionmentioning
confidence: 62%
“…17 A multicentric research in the Kingdom of Saudi Arabia including 992 cases with various psychiatric illnesses concluded a 41.2% prevalence of metabolic syndrome, according to the IDF diagnostic criteria. 18 Prevalence of specific metabolic abnormalities was evaluated in the Saudi sample, including central obesity (42.2%), raised blood pressure (42.5%), raised fasting blood glucose (47.8%), and low HDL cholesterol levels (52.5%). 18 A Palestinian study focused on 250 cases with schizophrenia and determined a 43.6% prevalence rate of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…18 Prevalence of specific metabolic abnormalities was evaluated in the Saudi sample, including central obesity (42.2%), raised blood pressure (42.5%), raised fasting blood glucose (47.8%), and low HDL cholesterol levels (52.5%). 18 A Palestinian study focused on 250 cases with schizophrenia and determined a 43.6% prevalence rate of metabolic syndrome. 19 It is therefore evident that there is a notable variation in the research methodology such as sample size and sampling techniques, as well as the difference in the diagnostic criteria used among published research; the finding from the current research consistently shows higher rates in comparison with the international and regional literature.…”
Section: Discussionmentioning
confidence: 99%